BEHAVIOR OF WASTE MANAGEMENT AT SEI KORONG. JILATANG KENAGARIAN CAMPAGO KECAMATAN V KOTO KAMPUNG DALAM PADANG PARIAMAN - Hary Budiman (Menara Ilmu, 2018)
Health development is the most important part of national development. The purpose of the development of health is to increase awareness, willingness, and healthy living ability for each person in order to realize optimal public health status. The success of health development plays an important role in improving the quality and competitiveness of Indonesian human resources. Based on data of garbage problem in Korong Sei. Jilatang of 64 (97.0%) where the surrounding environment is a lot of piles of waste bushes and on the road they consider the waste is a small thing that does not affect the health. The habit of Sei society. Jilatang this also includes bad where they like piling garbage in the house until many days. The number of cases of diarrhea and isp diseases can indirectly be caused by waste. It is expected that Walinagari to propose local regulations on waste management, create community working groups that care about health to make waste useful. To the community to apply the principle of 4R (Reduce, Reuse, Recycle, Replace) to break the chain of disease transmission Keywords: Waste management